2018
DOI: 10.1186/s13661-018-1062-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Rosseland thermal radiation and energy dissipation effects on entropy generation in CNTs suspended nanofluids flow over a thin needle

Abstract: In this paper, we examine thermal radiation effect of the nonlinear form on the dissipative nanofluids containing carbon nanotubes past a moving horizontal thin needle. We also perform a second law analysis with viscous dissipation. Single-wall carbon nanotube and multiple-wall carbon nanotube drop in H 2 O base fluid. Introducing suitable dimensionless variables, we reduce the governing equations to self-similar nonlinear differential equations. Matlab in-built boundary value solver bvp4c and shooting method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…The nonlinear differential equations (ODEs) (12)- (17) with the boundary constraints (18) are solved numerically R-K with shooting method. Initially, the set of nonlinear ODEs…”
Section: Methods Of Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonlinear differential equations (ODEs) (12)- (17) with the boundary constraints (18) are solved numerically R-K with shooting method. Initially, the set of nonlinear ODEs…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…The area of nanofluid attained greatly consideration owing to its great presentation in industrial, manufacturing and sciences like solar energy, biomedicine, chilling of electronic equipment, heat exchangers, shrinking and evaporating systems, innumerable chemical developments etc. Allured by these uses researchers [13][14][15][16][17][18][19][20] inspected the domain of nanofluids experimentally and numerically. Later on, Nagendramma et al [21] studied the magnetohydrodynamic double stratified hyperbolic fluid past a stretched permeable cylinder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xia et al deliberated the sway of four dissimilar surfactants on the constancy of MWCNTs with volume fraction (0.005%–0.2%) at subatmospheric pressure of 10 −3 Pa in a confined space and observed that the values of boiling heat transfer coefficient escalate with the rising volume fraction of nanoparticle values. Afridi et al has examined the steady flow of MWCNTs and SWCNTs with water as base fluid over a horizontally moving thin needle with nonlinear thermal radiation. Hussien et al numerically studied convective flow and heat transfer augmentation of GNPs/MWCNTs mixture nanofluid and minitube.…”
Section: Introductionmentioning
confidence: 99%
“…After the pioneering work of Bejan [1], analysis of entropy generation in fluid flow problems are reported by many researchers. Recently, Afridi et al [2] studied the entropy generation of carbon nanotubes CNTs nanofluids in a flow over a thin needle by incorporating the effects of nonlinear thermal radiation and viscous dissipation. Makinde [3] reported the effects of variable viscosity on inherent irreversibility in a flow over a flat plate with Newtonian heating and uniform magnetic field.…”
Section: Introductionmentioning
confidence: 99%